Proses Metalurgi Serbuk Komposit Matrik Phenolic Resin di Perkuat Serbuk Logam & Arang Tempurung Kelapa - Fibry Yansha; Sukanto Sukanto; Sugiyarto Sugiyarto (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study aims to investigate the effect of sintering temperature variations on the hardness and density of brake pad composites fabricated using the powder metallurgy method. The fabrication process consisted of material preparation, powder mixing, cold compaction, and sintering with the weight fraction of matrix and filler wt.% being 40/60, 48/52, and 56/44 wt.%. Powder mixing was carried out using a horizontal ball mill with a ball-to-powder weight ratio (BPR) of 10:1, a rotational speed of 90 rpm, and a milling time of 4 hours. Cold compaction was performed uniaxially at a pressure of 5300 PSI for 10 minutes, followed by sintering at temperatures of 50°C, 60°C, and 70°C for 10 minutes. Density testing was conducted based on Archimedes’ principle in accordance with ASTM B962-17, while hardness was measured using a portable Brinell hardness tester following ASTM E110-14. The highest hardness value of 103.0 HB was obtained at 48% matrix composition with a sintering temperature of 60°C, while the highest density of 1.453 g/cm³ was achieved at 40% matrix composition with a sintering temperature of 70°C. These findings demonstrate that sintering temperature has a significant influence on the mechanical and physical properties of the brake pad composite.